Deskripsi Employee Engagement, Job Satisfaction, dan Turnover Intention Karyawan di Sadara Resort - Ni Wayan Manik Kristya Dewi; I Gusti Lanang Suta Artatanaya; Cokorda Istri Sri Widhari (Economic Reviews Journal, 2026)
The hospitality industry is a service sector that strongly depends on the quality of human resources in delivering customer services. High work demands in this industry require companies to pay attention to employee conditions, particularly employee engagement, job satisfaction, and turnover intention. Sadara Resort, as a hospitality company, needs to understand these aspects to develop appropriate human resource management strategies. This study aimed to describe the levels of employee engagement, job satisfaction, and turnover intention among employees at Sadara Resort. A quantitative approach with a descriptive research design was employed. The study involved 51 employees selected as respondents. Data were analyzed using descriptive statistical methods. The findings revealed that employee engagement achieved a mean score of 3.61 and was categorized as good. Job satisfaction obtained a mean score of 3.61, also categorized as good. Meanwhile, turnover intention recorded a mean score of 2.94 categorized as moderately good, indicating that employees still show a tendency to leave the organization due to work-related and personal factors. The results are expected to provide useful insights for Sadara Resort management in improving employee engagement and job satisfaction while minimizing turnover intention.